Crystal structure, magnetic and catalytic oxidation properties of manganese(iii) tetrakis(ethoxycarbonyl)porphyrin. Issue 118 (13th November 2015) - Wang, Hua-Hua; Yuan, Hui-Qing; Mahmood, Mian H. R.; Jiang, Yi-Yu; Cheng, Fan; Shi, Lei; Liu, Hai-Yang
Abstract : 5, 10, 15, 20-tetrakis(ethoxycarbonyl)porphyrin manganese(iii ) chloride (Mn III TECPCl) existed as a Mn–O coordinated dimer. Mn III TECPCl gave high yield in oxidation of styrene by using TBHP or PhIO oxidant and was found recyclable. Abstract : A new meso -tetraalkyl porphyrin manganese complex, 5, 10, 15, 20-tetrakis(ethoxycarbonyl)porphyrinatomanganese (Mn III TECPCl), had been prepared and characterized by X-ray structure determination. Mn III TECPCl exists as a coordinated dimer in its crystal structure with a weak antiferromagnetic coupling between two Mn(iii ) ions. The catalytic oxidation of styrene by Mn III TECPCl was carried out in acetonitrile. Mn III TECPCl was found to be recyclable with a high conversion efficiency when using TBHP as an oxidant and the major product was benzaldehyde. Mn III TECPCl was also reusable by using an PhIO oxidant, but the major products turned out to be phenyl acetaldehyde and styrene epoxide.